An intrinsic value of the inhabitants’ sense of place in sustaining Dalem in Yogyakarta (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The persistent existence of the Keraton Yogyakarta has fundamentally catalyzed the growth of the Kraton District as a premier destination for cultural heritage tourism. Ensuring the long-term sustainability of this historic precinct necessitates a strategic prioritization of its inherited cultural values. A primary manifestation of the Sultanate’s historical power is the noble residential typology known as the Dalem. Both Dalem Mangkubumen and Dalem Kaneman serve as quintessential heritage assets that have endured by dynamically adapting to contemporary urban contexts to facilitate relevant communal activities. These structures possess an intrinsic value that reinforces their significance within the collective meaning-making processes across successive generations and historical narratives. This research investigates the intrinsic dimensions of the inhabitants’ sense of place by analyzing two primary constructs: place meaning, articulated through empirical experience and spatial satisfaction, and place attachment, expressed through self-identity and functional dependence. Utilizing a qualitative methodology, the study synthesizes field surveys including systematic observation and in-depth interviews with comprehensive literature reviews. The findings reveal that the Dalem maintains its intrinsic vitality through embedded cultural codes that link the residence to the broader Keraton ecosystem, manifested through the interrelation of meaning and attachment. Ultimately, socio-cultural practices function as the essential mechanisms for reproducing a sense of place and ensuring the intergenerational transfer of these intrinsic values.
Keywords: Cultural values; Dalem; Inhabitants; Sense of place; Socio-cultural practices